2011
DOI: 10.2139/ssrn.1736737
|View full text |Cite
|
Sign up to set email alerts
|

Speculators, Prices and Market Volatility

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
84
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 24 publications
14
84
2
2
Order By: Relevance
“…5 Brunetti et al (2010) also find that speculative activity in five different futures markets (including crude oil) does not lead price changes, but reduces risk by enhancing market liquidity.…”
Section: Introductionmentioning
confidence: 88%
“…5 Brunetti et al (2010) also find that speculative activity in five different futures markets (including crude oil) does not lead price changes, but reduces risk by enhancing market liquidity.…”
Section: Introductionmentioning
confidence: 88%
“…The so-called "financialization" hypothesis claims that volatile liquidity flows and rebalancing of portfolios have caused commodity markets to be more exposed to shocks and price movements at other financial markets (Basak und Pavlova 2014). Holding grains for financial portfolio diversification may not necessarily increase grain price volatility (Vercammen and Doroudian 2014), and empirical studies have yet to reach a consensus about the impacts of speculation and financialization on volatility (Brunetti et al 2011;Irwin and Sanders 2012;Tadesse et al 2014); however, some studies have found indications of volatility transmission (Tang und Xiong 2012). While this debate continues, it is important to note that futures markets (that involve also the participation of risk-loving speculators as contracting party to risk-averse hedgers) are crucial to coordinate supply and demand over time.…”
Section: Governmental Institutionsmentioning
confidence: 99%
“…Second, commodity-equity linkages fluctuate much more than the linkages between some other asset classes, offering fertile ground for an analysis of what (macroeconomic fundamentals, trading, or both) predicts those fluctuations. 2 Third, we seek to add not only to the asset pricing literature but also to a fastgrowing literature on the financialization of commodity markets -see, e.g., Acharya, Lochstoer & Ramadorai (2011), Brunetti, Büyük!ahin & Harris (2011), Brunetti and Reiffen (2011), Büyük!ahin, Haigh, Harris, Overdahl & Robe (2009), , Cheng, Kirilenko & Xiong (2012), Etula (2010), Hamilton and Wu (2012), Henderson, Pearson & Wang (2012), Hong and Yogo (2012), Irwin and Sanders (2012), Kilian and Murphy (2012), Korniotis (2009), Singleton (2013), Stoll and Whaley (2010), or Tang and Xiong (2012). This paper contributes to the debate on the financialization of commodities by identifying a relationship between financialization and the intensity of cross-market linkages.…”
Section: Introductionmentioning
confidence: 99%